2014
DOI: 10.1002/ajmg.b.32265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of negative stressors on DNA methylation in the brain: Implications for mood and anxiety disorders

Abstract: Stress is a major contributor to anxiety and mood disorders. The recent discovery of epigenetic changes in the brain resulting from stress has enhanced our understanding of the mechanism by which stress is able to promote these disorders. Although epigenetics encompasses chemical modifications that occur at both DNA and histones, much attention has been focused on stress-induced DNA methylation changes on behavior. Here, we review the effect of stress-induced DNA methylation changes on physiological mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 143 publications
(183 reference statements)
0
22
0
Order By: Relevance
“…Examination of the methylation status of risk genes in psychiatric illness may provide an additional indicator of gene expression (Hing et al, 2014). One study has reported that OXTR is more highly methylated in subjects with anorexia than healthy women (Kim et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the methylation status of risk genes in psychiatric illness may provide an additional indicator of gene expression (Hing et al, 2014). One study has reported that OXTR is more highly methylated in subjects with anorexia than healthy women (Kim et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Stress is a critical environmental trigger for the development of depression, anxiety, cardiovascular diseases, immunity disorders and others (Goodman et al, 2012;Hing et al, 2014;Kario et al, 2003;Meyer and Hamel, 2014;Sterner and Kalynchuk, 2010). Pyrethroid insecticides release noradrenaline and adrenaline (de Boer et al, 1988) and increase anxiety (De Souza Spinosa et al, 1999;Moniz et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly applied to humans, these studies investigate stress-induced DNA methylation (and other) processes in the brain that alter gene expression. These studies focus largely on genes related to HPA axis functions, neurotransmission, and neuroplasticity [54]. Environmentally (stress) induced DNA methylation has been shown to have both shortterm and long-term effects and in some instances intergenerational effects [55 ].…”
Section: Genetic Factorsmentioning
confidence: 99%